Plackett-Burman design for the optimization of a novel extracellular marine protease production - Dehimi, Maya; Yusof, Faridah (2020)
Proteases are protein degrading enzymes, widely used in many enzyme-based industries. The search for novel proteases never stops. Proteases from marine organisms have several advantages over the proteases obtained from the non-marine environment since their optimal temperatures and other enzymatic characteristics differ significantly. In this study, marine bacteria were isolated from sea water and sediments from the South China Sea to be investigated on their ability to produce extracellular protease on skim milk agar plates and the production was confirmed biochemically by the protease assays. Three bacterial strains identified as Bacillus safensis, Bacillus licheniformis and Staphylococcus warneri were selected and the protease production were optimized by running experiments using the Plackett-Burman design. This approach facilitated the study of the effect of a large number of variables spanned by many factors and their settings with a small number of experimental runs leading to a considerable economy in time and cost for the process optimization. Bacillus licheniformis had shown to be the highest yielding protease, whereby the production levels increased from 43.76 U/mL to 158.41 U/mL. Factors observed to be significant were the concentrations of CaCl2, the inoculum size and agitation rate. This information is important in the next level of the optimization processes.